Propensity to additions in service persons: an experience of historical research - Valery Naumov (Kazimierz Wielki University, 2016)
Background. The influence of extreme factors of military service on the adaptive capabilities and health of service persons is considered. As the modern living conditions are characterized by an increased number of emergencies and their consequences social strains, it is necessary to create actively functioning armed military units, including territories with local violent conflicts, to ensure law and order. The aim: to analyze the historical experience of different states on the study of service persons' addictive behaviour in different historic periods and battlelike situations. Results: It has been revealed that the features of the basic life support systems functioning in service persons who are under the conditions of violent conflicts make it possible to view the presence of significant changes in their state of health, up to pathological ones. The combating physiological stress, adaptive capabilities of service persons, psychosocial characteristics of the individuals predispose to addictive behavior. Conclusions: the researches made allow to offer some precautionary mechanisms of influence on service persons personality for preventing addictions and addictive behavior and its consequences.